Internal migration and life satisfaction: Well-being effects of moving as a young adult - Malgorzata Switek (Institute for the Study of Labor (IZA), 2012)
Migration typically leads to higher income, but its association with life satisfaction remains unclear. Is migration accompanied by an increase in life satisfaction? If it is, is the increase in income responsible or are other life domains driving the satisfaction changes? These two questions are addressed using longitudinal data from a Swedish Young Adult Panel Study for 1999 and 2009. Comparing migrants to non-migrants, it is found that internal migration is accompanied by an increase in life satisfaction. This increase is observed for both, migrants who move due to work and those who move due to non-work reasons. This finding holds regardless of other life transitions that may accompany migration, such as marriage and joining the labor market. However, different factors account for the increase in life satisfaction for work and non-work migrants. For non-work migrants, it is greater housing satisfaction that leads to an improvement in life satisfaction. Moreover, no increase in income relative to non-migrants is found for this group. For work migrants, although their income increases compared with non-migrants, this increase does not seem to explain the differential improvement in life satisfaction because of a lack of improvement in their economic satisfaction (compared to non-migrants). Rather, it is the higher relative status arising from occupational advancement that seems to contribute to the higher life satisfaction for work migrants.
Keywords: J0; J61; O15; R23; 330; internal migration; life satisfaction; relative status; housing satisfaction